a) \(\dfrac{-2}{3}:x=\dfrac{-5}{6}\)
\(\Rightarrow x=\dfrac{-2}{3}:\dfrac{-5}{6}\)
\(\Rightarrow x=\dfrac{4}{5}\)
Vậy: \(x=\dfrac{4}{5}\).
b) \(5-\left(2x+1\right)^3=32\)
\(\Rightarrow\left(2x+1\right)^3=5-32\)
\(\Rightarrow\left(2x+1\right)^3=-27\)
\(\Rightarrow\left(2x+1\right)^3=\left(-3\right)^3\)
\(\Rightarrow2x+1=-3\)
\(\Rightarrow2x=-3-1\)
\(\Rightarrow2x=-4\)
\(\Rightarrow x=-4:2=-2\)
Vậy: \(x=-2\).
a)
\(\dfrac{-2}{3}:x=\dfrac{-5}{6}\left(x\ne0\right)\\ \Leftrightarrow x=\left(\dfrac{-2}{3}\right):\left(\dfrac{-5}{6}\right)\\ \Leftrightarrow x=\dfrac{-2}{3}.\dfrac{6}{-5}\\ \Leftrightarrow x=\dfrac{\left(-2\right).6}{3.\left(-5\right)}=\dfrac{4}{5}\left(tm\right)\)
b)
\(5-\left(2x+1\right)^3=32\\ \Leftrightarrow\left(2x+1\right)^3=-27\\ \Leftrightarrow\left(2x+1\right)^3=\left(-3\right)^3\\ \Rightarrow2x+1=-3\\ \Leftrightarrow2x=-4\\ \Leftrightarrow x=-2\)